2022
DOI: 10.1371/journal.pone.0261642
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to join community based health insurance among households in South Wollo, Northeast Ethiopia: A community-based cross-sectional study

Abstract: Background Poor health care financing remains a major challenge to health service utilization among the lower socioeconomic society. Consequently, countries have designed different health insurance programs to overcome financial barriers against health services utilization. Similarly, Ethiopia has been implementing community-based health insurance programs since 2011 to improve health care financing system. However, only a small number of people are enrolled which might be attributed to lack of willingness tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Urban household heads are 1.484 times less likely to join the scheme compared to rural household heads (AOR = 1.484; 95% CI: 2.343-6.427). The present findings are consistent with the study done in South Wollo, Northeast Ethiopia, where rural households are two times more likely to joined a CBHI scheme compared to urban households (Biset Wagaw et al, 2022). The findings stand in contrast to a study in Kenya, which found that urban households were more likely than rural households to enroll in the health insurance plan (Kimani et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Urban household heads are 1.484 times less likely to join the scheme compared to rural household heads (AOR = 1.484; 95% CI: 2.343-6.427). The present findings are consistent with the study done in South Wollo, Northeast Ethiopia, where rural households are two times more likely to joined a CBHI scheme compared to urban households (Biset Wagaw et al, 2022). The findings stand in contrast to a study in Kenya, which found that urban households were more likely than rural households to enroll in the health insurance plan (Kimani et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…7 Despite the fact that many of the sub-regional countries' social health interventions are majorly for the poor and intended to connect the gap linking access to and utilization of health care commodities, including immunization of children. [41][42][43] Research evidence have shown that rich people in the society tend to profit more from such intervention strategies at the expense of the poor people of the society who may actually be the targeted population for the interventions. 44 Globally, inadequate living conditions pose a high-risk factor for negative health condition and are linked to insufficient use of primary health care.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of African nations still rely on OOP healthcare, which affects the frequency of use of health services among impoverished rural communities, ultimately affecting the strategy for achieving UHC ( 4 ). Community-based health insurance (CBHI) has been established in LMICs to reduce OOP healthcare costs and promote the use of health services to attain the UHC objective ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…More than half of African nations still rely on OOP healthcare, which affects the frequency of use of health services among impoverished rural communities, ultimately affecting the strategy for achieving UHC ( 4 ). Community-based health insurance (CBHI) has been established in LMICs to reduce OOP healthcare costs and promote the use of health services to attain the UHC objective ( 4 , 5 ). The CBHI is a voluntary, non-profit insurance that consolidates premium payments from members into a common fund and covers essential medical expenses at nearby clinics when a member falls ill ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation